815 Improving staff perspectives on managing dystonia in general paediatrics. (17th August 2022) - Alexander, Laith; Leslie, Ross; Tran, Tien; Ramachandran, Rohana; Lumsden, Daniel
Abstract : Aims: We aimed to improve the confidence of medical and nursing staff working in General Paediatrics at a tertiary centre in managing dystonia. Methods: Data were collected over three 'Plan, Do, Study, Act' cycles ( figure 1 ). Baseline data were collected regarding staff members' confidence in managing dystonia; how often patients had a personalised dystonia plan; and how often the named Paediatric Neurology Consultant responsible for the patient's dystonia was known. In cycle one, educational posters were circulated and an email address for direct communication with the Paediatric Neurology team was established, enabling concerns to be addressed quickly. In cycle two, personalised dystonia plans were made using a standard format ( figure 2 ) and kept in patient's notes, a Link Nurse was allocated, and teaching sessions were given to the medical team. Cycle three, which is in progress, will extend the teaching to the nursing team, add educational videos to the Trust online education platform, and explore options to ensure each patient's dystonia plan remains associated with their electronic patient record across every inpatient admission. Results: At baseline (n=35), 37.1% (13/35) of staff felt confident in managing dystonia (either 'agree' or 'strongly agree'). Only 2.9% (1/35) thought all patients had a personalised dystonia plan. Finally, 17.1% (6/35) of staff agreed or strongly agreed that they knew whom the patient's named Consultant responsible for their dystonia management. After cycle two (n=24), 41.6% (10/24) of staff felt confident managing dystonia (4.5% improvement), 16.7% (4/24) felt that all patients with dystonia had a personalised plan (13.8% improvement) and 20.8% (5/24) typically knew the patient's named Consultant (3.7% improvement). Re-auditing after six months (n=18) demonstrated that staff confidence had fallen, with 27.8% (5/18) feeling confident in managing dystonia, which may be contributed to by a lower proportion of responses from medical staff (38.9%, compared with 58.3% when confidence was highest, after cycle two), indicating a need to address confidence among nursing and allied health professional team members. The drop was also associated with the changeover of trainees suggesting the teaching needs to be regularly embedded into six monthly cycles to allow for the changeover. Clarity of the named Consultant for each patient had been maintained, with 22.2% (4/18) typically knowing the named Consultant. However, only 5.6% (1/18) of staff felt all patients with dystonia had personalised plans in place. Conclusion: By implementing personalised plans for dystonia management; educating staff on the use of a step-wise, systematic approach to management; and by minimising barriers to appropriate escalation by use of a Link Nurse and specific email address, staff who are not Neurology specialists can be supported to feel more confident in managing worsening dystonia in General Paediatric settings. Further work will focus on extending teaching sessions for nursing and allied health professionals, build in a repeat cycle of training to capture new staff and self-directed learning they can access to refresh knowledge. Ensuring individual management plans are accessible and linked to patients over subsequent inpatient admissions, ideally by being linked electronically rather than paper charts is also key.